Cost and Effectiveness of Banking Sector Restructuring in Transition Economies - Zoli, Edda (IMF Working Papers; Working Paper ;, 2001)
The paper analyses the cost and effectiveness of bank restructuring policies in 11 transition countries during 1991-98. It argues that country-specific banking sector features, the size of bad loans inherited from the centrally planned system, and weaknesses in the restructuring policies implemented were the main factors affecting the overall fiscal costs, with the latter two being more significant. The paper finds no significant relationship between the size of restructuring costs and overall improvement in banking sector performance for the sample countries as a whole.